1997
DOI: 10.1007/s001250050738
|View full text |Cite
|
Sign up to set email alerts
|

Relatively more atherogenic coronary heart disease risk factors in prediabetic women than in prediabetic men

Abstract: Diabetes mellitus is associated with a marked increase in coronary heart disease (CHD) [1,2]. In many [1,[3][4][5][6][7] but not all [8][9][10][11] studies this excess risk of CHD is relatively higher for female diabetic subjects than for male diabetic subjects. The reasons for the excess risk of CHD in diabetic subjects are multifactorial but include dyslipidaemia, hypertension, and insulin resistance. In some cases, the increase in these risk factors may be relatively greater in female diabetic subjects than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 39 publications
3
59
1
2
Order By: Relevance
“…It is unclear whether these factors act differentially in women versus men, but our findings and those of others suggest that there may be some pathophysiological differences between sexes. Indeed, Haffner et al (14) have shown that diabetic women tend to be older and tend to have a higher likelihood of associated hypertension than do their male counterparts. Also, the relationship between diabetes and endothelial function may interestingly vary between sexes, as revealed in an elegant study by Steinberg et al (15) showing that diabetes is an important predictor of endothelial dysfunction in women, while obesity is a more important contributor to endothelial dysfunction in men.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether these factors act differentially in women versus men, but our findings and those of others suggest that there may be some pathophysiological differences between sexes. Indeed, Haffner et al (14) have shown that diabetic women tend to be older and tend to have a higher likelihood of associated hypertension than do their male counterparts. Also, the relationship between diabetes and endothelial function may interestingly vary between sexes, as revealed in an elegant study by Steinberg et al (15) showing that diabetes is an important predictor of endothelial dysfunction in women, while obesity is a more important contributor to endothelial dysfunction in men.…”
Section: Discussionmentioning
confidence: 99%
“…However, a gender-specific effect of chronic inflammation on insulin resistance might help to explain the results from the San Antonio Heart Study that showed that women who developed diabetes experienced a greater change in MetS-associated risk factors compared with the corresponding group of men. 31 The same pathobiology might help to explain why the development of diabetes is associated with a greater increase in dyslipidemia and relative risk for CVD in women than in men. 32,33 …”
Section: Gender Influencementioning
confidence: 99%
“…Although most women with GDM return to normal glucose tolerance after delivery, it is well established that glucose intolerance detected during pregnancy is predictive of later maternal type 2 diabetes (10,11). Particularly, women with impaired glucose metabolism or diabetes carry a greater cardiovascular risk than normoglycemic individuals (12). Indeed, women with prior GDM (pGDM) feature endothelial dysfunction that is associated with insulin resistance (13)(14)(15) and obesity, which are the most prominent risk factors for GDM and type 2 diabetes in pGDM and linked to both inflammatory processes and angiopathy (16).…”
mentioning
confidence: 99%